Mathematical connections made during investigative tasks in statistics and probability - Liezl Joy Lazaro Quilang; Lyndon Laborte Lazaro (Institute of Advanced Engineering and Science, 2022)
The Philippines has undergone a fundamental overhaul of its educational system to highlight basic education and overcome its deficiencies. The educational reform prompts prospective teachers to connect the concepts taught to instill a more profound understanding. As such, the researchers explored the mathematical connections made by prospective secondary mathematics teachers while completing investigative tasks. The study employed a concurrent triangulation mixed-methods design. Data were gathered from 39 prospective secondary mathematics teachers enrolled in the state universities' flagship campuses in Northeastern Philippines. Data were gathered using mathematical connections evaluation, think-aloud strategy, and interviews. Frequency counts, percentages, mean percent scores, Pearson product-moment correlation coefficient, and analysis of the interviews' transcriptions were employed in the study. Results showed that the prospective teachers performed best in making instruction-oriented connections but have difficulty in making implications connection. Also, the prospective teachers' ability to successfully make the mathematical connection is directly linked to their knowledge of the concept, the algorithm, and the part-whole relationship. As such, reform efforts should be made to enhance mathematical connections, emphasizing statistical thinking, and reasoning. Moreover, higher education institutions should incorporate connecting as one of the intended learning outcomes for prospective mathematics teachers.